Konstruksi Sosial Pernikahan Jarak Jauh (Long Distance Marriage) Masyarakat Desa Jenangan - Yuliantika, Nias; Rohmanu, Abid (MAHAKIM Journal of Islamic Family Law, 2025)
This study aims to understand the social construction of long-distance marriage (LDM) in Jenangan Village using the social construction theory of Peter L. Berger and Thomas Luckmann, this research was conducted with a qualitative approach, through interviews and documentation as data collection methods. The results show that the social construction of long-distance marriage goes through three stages: externalization, objectivation, and internalization. Long-distance marriage (LDM) in Jenangan Village is socially constructed as a valid and accepted choice, with the main focus on fulfilling the family's economic needs. The people of Jenangan Village recognize that LDM is a reality that requires high commitment and patience. Externalizing actions, such as choosing LDM to meet economic needs, has become an objectively accepted norm in the community. Although challenges such as limited communication and lack of togetherness are part of the reality, this social norm is internalized by individuals who live it as part of the way to achieve economic goals and realize their dreams.